COMPARATIVE EFFECT OF INHALING CORTICOSTEROIDS IN DIFFERENT DOSES AND DURATIONS WITH RISK OF DIABETES MELLITUS TYPE 2 IN CHRONIC ASTHMA PATIENTS (The Research of Medical Science Review, 2025)
Asthma is a heterogeneous disease identified by chronic inflammation, airway hyperresponsiveness. The occurrence of exacerbations is a main parameter for asthma control. Recent research depicts that there is a link of ICS therapy and diabetes in asthmatic patients. In patients with type-2 diabetes who were mainly taking ICS for lung related disorders were found to show a higher (HbA1c) level than those who did not consume ICS. Recent studies suggests that disorders of glucose metabolism are associated with worsening of asthma. (ICS) are the spine of treatment for patients with asthma. In small comparative study in patients with type 2 diabetes mellitus glycosylated hemoglobin levels showed a noticeable increase in levels pointedly after 6 weeks of treatment with inhaled fluticasone, these observations suggest that ICS may exacerbate diabetes in asthma by increasing blood glucose levels in patients. The aim of the study is to assess the complication effect of inhaling corticosteroids in Diabetes mellitus type 2 patients with chronic asthma patients since different durations (1 year, 5-year, 10-year post asthma).